Comparison between different methods of estimating the developmental stages in a synanthropic scorpion Tityus stigmurus (Thorell, 1876) - Kleber Agari Campos; Eunice Aparecida Bianchi Galati; André Felipe Araújo Lira (Acta Scientiarum. Biological Sciences, 2024)
Determining developmental stages is an important tool for monitoring populations of medically important arthropods, including some scorpions species. Therefore, prediction tools for scorpion developmental stages may provide useful information for public health. Thus, this study compared different methods to estimate the developmental stages of the alien and medically important scorpion species Tityus stigmurus collected in São Paulo. We tested the applicability of the following morphometric methods: grouping (K-means and Ward’s), theoretical, and distribution of frequencies for instar estimation in field-caught T. stigmurus individuals. The methods showed similar results up to the 5th instar. Our results corroborate the literature on the non-objectivity of the hierarchical clustering method in determining the exact number of size classes in the sample. We also found that the hierarchical and non-hierarchical clustering methods diverged regarding the two largest size classes. The peaks in the frequency curve of the carapace length and the theoretical calculation using a growth factor of 1.26 proved useful in determining the stages of development. Seven size classes were demonstrated, which provide evidence that T. stigmurus individuals can reach maturity at the 6th or 7th instar.